Peranan Bagian Operasional dalam Memonitoring Keberangkatan Kapal Milik oleh PT. Baruna Mitra Segara Lines Bandar Lampung - Eliasaf Maduwu; Syarifur Ridho; Dina Rispianti (Jurnal Strategi Bisnis Teknologi, 2025)
The operational department at PT. Baruna Mitra Segara Lines Bandar Lampung plays a crucial role in ensuring the timely departure of ships. This study examines how the department monitors ship departures to ensure they occur on time and follow established procedures. The research uses a qualitative case study approach, collecting data through observation and documentation. The findings show that active involvement from the operational department helps reduce technical and administrative issues that may delay departures. Improving human resources and operational systems is essential to guarantee smooth operations. The operational department is responsible for coordinating between departments, checking ship readiness, and monitoring schedules. The department's effectiveness significantly reduces delays and enhances customer satisfaction. The study also highlights that the accuracy of operational work impacts the efficiency, safety, and reliability of the shipping process. Strengthening the monitoring system and improving human resource quality are critical to optimizing the department’s role. However, challenges such as limited resources and outdated information systems need to be addressed to improve performance. This research aims to provide insights for PT. Baruna Mitra Segara Lines management to enhance the operational process of ship departures.